IMPROVING THE FUNCTIONAL SKILLS OF THE BELT WRESTLER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article, the method of preparing athletes for the competition by controlling the ability to perform work and improving the performance skills of wrestlers during the training of belt wrestlers and reserve athletes is researched.